The Elephant in the Room. Some Observations on Animal (and Robot) Rights (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The Italian Constitution was recently amended to include «animal protection» as a subject over which the State has exclusive legislative power (see art. 9, par. 3). The aim of this paper is to explore the possible ramifications and long-term impact of this apparently small modification, specifically on animal law and policy. Will animal personhood and rights become a reality? And would such a change be in line with the constitutional order? Finally, could the animal-robot analogy prove useful, when problematizing the legal thinghood of animals and exploring the feasibility of animal (and robot) rights?
Keywords: Animals; legal personhood; animal rights; robot rights; ethics of care